Online Based Thesis Guidance Application For Informatics Students During Pandemic - Hermawan, Latius; Ismiati, Maria Bellaniar (Jurnal Transformatika, 2021)
The Ministry of Education and Culture (Kemendikbud) issued Circular Letter Number 15 of 2020 concerning Guidelines for Organizing Learning from Home in an Emergency for the Spread of Covid-19. This causes the learning process that should be done face-to-face, being changed to online. Students must study from home and carry out the online thesis guidance process. Some of the difficulties experienced by students during direct mentoring, namely the difficulty of meeting lecturers who are busy teaching or doing assignments from institutions, besides that students who come from outside the city have to go back and forth just to meet the supervisor.. One of the ways to solve this problem is by applying technology.   Currently there is web technology that can be used to easily develop applications, namely the concept of a framework approach. With the existence of an online-based application which is the role of current technological developments, it will make the thesis guidance process carried out by lecturers and students more flexible. Students are able to carry out the guidance process anywhere and anytime.